2015
DOI: 10.2174/2211536604666150131125805
|View full text |Cite
|
Sign up to set email alerts
|

Methylated MicroRNA Genes of the Developing Murine Palate

Abstract: Environmental factors contribute to the etiology of cleft palate (CP). Environmental factors can also affect gene expression via alterations in DNA methylation suggesting a possible mechanism for the induction of CP. Identification of genes methylated during development of the secondary palate provides the basis for examination of the means by which environmental factors may adversely influence palatal ontogeny. We previously characterized the methylome of the developing murine secondary palate focusing primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…miRs have been implicated in developmental processes and various types of cancers ( Mukhopadhyay et al, 2010 ; Chen et al, 2012 ), and dysregulation of miR expression has been identified in a variety of human diseases ( Mendell and Olson, 2012 ). Recent studies show that miRs play important roles in craniofacial development ( Shin et al, 2012 ; Seelan et al, 2014 ; Warner et al, 2014 ; Mukhopadhyay et al, 2019 ); for example, administration of miR-23b and miR-133 duplex results in facial defects in zebrafish ( Ding et al, 2016 ). A bioinformatic study suggested that miR-199a-5p may be associated with CL/P through the modulation of transforming growth factor (TGF)-α expression ( Chen et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miRs have been implicated in developmental processes and various types of cancers ( Mukhopadhyay et al, 2010 ; Chen et al, 2012 ), and dysregulation of miR expression has been identified in a variety of human diseases ( Mendell and Olson, 2012 ). Recent studies show that miRs play important roles in craniofacial development ( Shin et al, 2012 ; Seelan et al, 2014 ; Warner et al, 2014 ; Mukhopadhyay et al, 2019 ); for example, administration of miR-23b and miR-133 duplex results in facial defects in zebrafish ( Ding et al, 2016 ). A bioinformatic study suggested that miR-199a-5p may be associated with CL/P through the modulation of transforming growth factor (TGF)-α expression ( Chen et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of microRNAs (miRs), which are small non-coding RNAs (21–25 nucleotides) that regulate the expression of target genes at the post-transcriptional level ( Hudder and Novak, 2008 ; Hou et al, 2011 ), play important roles in a wide array of cellular functions during the development of various tissues, including the upper lip and the palate ( Shin et al, 2012 ; Seelan et al, 2014 ; Warner et al, 2014 ; Mukhopadhyay et al, 2019 ). For instance, loss of a miR-processing enzyme, such as DROSHA and DICER, results in craniofacial developmental defects in mice ( Zehir et al, 2010 ; Nie et al, 2011 ; Schoen et al, 2017 ), and polymorphisms in DROSHA are associated with risk of CL/P in humans ( Xu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Maternal use and exposure to tobacco, alcohol, drugs (e.g., retinoic acid and dexamethasone), and chemicals (e.g., dioxin and heavy metals), as well as mutations in genes related to the degradation/metabolism/release of these teratogens, are considered to be risk factors (Prescott et al, 2002;Chevrier et al, 2005;Ramirez et al, 2007). An increasing number of studies suggest that microRNAs (miRs), which are endogenous small non-coding RNAs (∼22 nucleotides long) that negatively regulate the expression of their target genes (Bartel, 2004;Obernosterer et al, 2006), play important roles in normal palate development and CL/P in humans and mice (Karsy et al, 2010;Shin et al, 2012;Seelan et al, 2014;Chung et al, 2016;Schoen et al, 2017Schoen et al, , 2018Wang et al, 2017;Mukhopadhyay et al, 2019); however, it remains elusive how and which miRs are crucial roles in CL/P. Our recent studies show that overexpression of either miR-140-5p, miR-133b, miR-374a-5p, miR-381-3p, or miR-4680-3p suppresses cell proliferation in cultured human embryonic palatal mesenchymal (HEPM) cells (Li et al, 2019;Suzuki et al, 2019), suggesting that these miRs may be involved in the pathogenesis of cleft palate.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, knowledge of new types of RNA with regulatory functions, located in non-coding regions of DNA, has improved our understanding of gene expression regulation (Scherrer, 2018). Many different microRNAs have been identified to temporally and spatially regulate morphogens and transcription factors during palatogenesis (Eberhart et al, 2008;Seelan et al, 2014;Ding et al, 2016;Reiss and Bhakdi, 2017;Schoen et al, 2017). Not surprisingly, microRNAs have been suggested as be new targets for investigating in CL/P studies (Li et al, 2010;Wang et al, 2013Wang et al, , 2017Ma et al, 2014;Gao et al, 2015;Li D. et al, 2016;Li J. et al, 2016;Schoen et al, 2017Schoen et al, , 2018Chen et al, 2018;Grassia et al, 2018;Pan et al, 2018;Suzuki et al, 2018;Wu N. et al, 2018;Xu M. et al, 2018).…”
Section: Ecm Structural Molecules and Soluble Factorsmentioning
confidence: 99%